Effect of tannin from blackberry (Syzigium cumini) seed on in vitro rumen fermentation (Progressive Agriculture, 2015)
An experiment was conducted to quantify the chemical composition, different forms of tannins and their effects on in vitro gas production, organic matter digestibility and metabolisable energy content in Syzigium cumini (Blackberry) seed with and without polyethelene glycol (PEG). The DM, OM, ash, CP, NDF and ADF contents of S. cumini seeds were 90.1, 87.6, 2.6, 4.6, 32.9 and 15.5%, respectively. The total phenol, total tannin, condensed tannin and hydrolysable tannin content were 5.89, 4.25, 0.42 and 0.05mg/g seed, respectively. In vitro gas production, organic matter digestibility and metabolisable energy content of S. cumini seed were 54 ml, 42.91% and 6.43 MJ/Kg DM, respectively. Addition of PEG to tannin containing seed was significantly (P